2014
DOI: 10.1007/s12034-014-0623-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thickness on electronic structure of titanium thin films

Abstract: Effects of thickness on the electronic structure of e-beam evaporated thin titanium films were studied using near-edge X-ray absorption fine structure (NEXAFS) technique at titanium L 2,3 edge in total electron yield (TEY) mode and transmission yield mode. Thickness dependence of L 2,3 branching ratio (BR) of titanium was investigated and it was found that BR below 3•5 nm shows a strong dependence on film thickness. Mean electron escape depth (λ) in titanium, an important parameter for surface applications, wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous studies showed that increase of 3d electrons spatial localization causes growth of the BR as the screening of the 2p -3d interaction becomes weaker. [63][64][65][66] This phenomenon was observed for a wide set of 3d TMs in thin layers with different thickness 63,65,66 and clusters of different size. 64 In both systems, increase of the layer thickness or cluster radius leads to gradual decrease in the BR.…”
Section: Branching Ratio Analysismentioning
confidence: 68%
“…Previous studies showed that increase of 3d electrons spatial localization causes growth of the BR as the screening of the 2p -3d interaction becomes weaker. [63][64][65][66] This phenomenon was observed for a wide set of 3d TMs in thin layers with different thickness 63,65,66 and clusters of different size. 64 In both systems, increase of the layer thickness or cluster radius leads to gradual decrease in the BR.…”
Section: Branching Ratio Analysismentioning
confidence: 68%
“…An additional 100 nm thick Al layer is prepared on top of Au and Ti. Although the Ti layer is relatively thinner than the other metal layers, its electrons state should be comparable to that of the thicker, e.g., 10 nm, Ti film 19 so that its covalent bonding ability with the WSe 2 layer is guaranteed.
Figure 2( a–c ) Optical images of WSe 2 flakes prepared on an Al 2 O 3 substrate. ( d – f ) Time-domain thermoreflectance mapping results for Al/WSe 2 /Al 2 O 3 , Al/Au/WSe 2 /Al 2 O 3 , and Al/Ti/WSe 2 /Al 2 O 3 .
…”
Section: Distinct Thermal Properties Of the Mono- And Bi-layered Wse2mentioning
confidence: 99%